The Effect of Training Strategies on the Performance of Trainees in the Kingdom of Saudi Arabia - ALFAQEIN, Omar Saeed; OMRAN, Abdelnaser; BADAWI, Ummalzayn Hussain (Journal of Advanced Research in Management, 2017)
Staff training is one of the common concerns in thought and management application of modern management in the first quarter of the last century. The awareness of the importance of the relationship between the training staff and their ability to invent new ways of doing business in these institutions is still limited. As noted, the trainees of the National Water Company (NWC) are inefficient in achieving customer service, maintaining the facilities, and repairing faults. Thus, this study aimed at identifying the effect of training strategies on the performance of trainees in NWC in Mecca city in the Kingdom of Saudi Arabia. A total of 100 closed-ended questionnaires were randomly distributed to employees such as managers, heads of departments, technicians, and workers, in NWC. Of these, only 85 questionnaires that were duly completed, and analysed, yielding a by Ads" href="#65254445"> response rate of 85%. Data were analysed statistically using SPSS software (Version 19.0). Findings in Mecca show that almost 50% of the development of human resources was explained by the training strategy. The two dimensions that were successfully predicted in the development of human resource were trainers and administrative and supervisory services. The study comes out with several recommendations. One of these recommendations is that NWC should obtain trainers from outside the company to improve the trainees’ expertise.